2003
DOI: 10.1016/s1010-7940(02)00864-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitral annuloplasty in patients with ischemic versus dilated cardiomyopathy

Abstract: Mitral reconstruction with a posterior annuloplasty using a flexible ring is effective in patients with severely depressed left ventricle function and has an acceptable operative mortality. Mid-term results are superior to medical treatment alone and comparable to cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 20 publications
2
41
0
8
Order By: Relevance
“…In our study, early mortality occurred in one patient in the MAP group (1.6%), and this is comparable to recent reports. 5,16,17) Regarding the indications for mitral valve procedures, Kang et al suggested that mitral valve repair was superior to CABG alone in patients with severe MR. However, in patients with moderate MR, the intraoperative mortality of mitral valve repair was higher than that of CABG alone, whereas MR improvement rates were similar in the two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, early mortality occurred in one patient in the MAP group (1.6%), and this is comparable to recent reports. 5,16,17) Regarding the indications for mitral valve procedures, Kang et al suggested that mitral valve repair was superior to CABG alone in patients with severe MR. However, in patients with moderate MR, the intraoperative mortality of mitral valve repair was higher than that of CABG alone, whereas MR improvement rates were similar in the two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, we must note that recurrent MR leads to the recurrence of CHF, as was the case with the patient with persistent MR. Szalay et al reported that preoperative NYHA functional class IV was the only risk factor of recurrent MR after MAP in idiopathic DCM. 7 In the current study, the patient with recurrent MR was in NYHA functional class IV and had the most severe CHF before surgery among all the patients. The severity of preoperative functional status might be a sign of recurrent MR.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, sheep with IMR had systolic and diastolic LV diameters (47Ϯ7 and 59Ϯ5 mm) similar to those observed in human IMR (50Ϯ1 and 64Ϯ1 mm). 25 That human clinical study with RT3D echo demonstrated increased mitral annular diameter and asymmetrical MV deformation (more severe tenting at the medial side than the lateral side) in IMR; in contrast, leaflet tenting was symmetrical in dilated cardiomyopathy. The present study in sheep with chronic IMR revealed similarities to human chronic IMR, including similar mitral annular dilatation and asymmetric MV deformation (more severe tenting at the medial than the lateral side).…”
Section: Discussionmentioning
confidence: 93%